Disparities in telephone CPR access and timing during out-of-hospital cardiac arrest. (June 2017) - Nuño, Tomas; Bobrow, Bentley J.; Rogge-Miller, Karen A.; Panczyk, Micah; Mullins, Terry; Tormala, Wayne; Estrada, Antonio; Keim, Samuel M.; Spaite, Daniel W.
Abstract: Aim: Spanish-only speaking residents in the United States face barriers to receiving potentially life-saving 911 interventions such as Telephone –cardiopulmonary resuscitation (TCPR) instructions. Since 2015, 911 dispatchers have placed an increased emphasis on rapid identification of potential cardiac arrest. The purpose of this study was to describe the utilization and timing of the 911 system during suspected out-of-hospital cardiac arrest (OHCA) by Spanish-speaking callers in Metropolitan Phoenix, Arizona. Methods: The dataset consisted of suspected OHCA from 911 centers from October 10, 2010 through December 31, 2013. Review of audio TCPR process data included whether the need for CPR was recognized by telecommunicators, whether CPR instructions were provided, and the time elements from call receipt to initiation of compressions. Results: A total of 3398 calls were made to 911 for suspected OHCA where CPR was indicated. A total of 39 (1.2%) were determined to have a Spanish language barrier. This averages to 18 calls per year with a Spanish language barrier during the study period, compared with 286 OHCAs expected per year among this population. The average time until telecommunicators recognized CPR need was 87.4 s for the no language barrier group compared to 160.6 s for the Spanish-language barrier group ( p < 0.001).Time to CPR instructions started was significantly different between these groups (144.4 s vs 231.3 s, respectively) ( p < 0.001), as was time to first compression, (174.4 s vs. 290.9 s, respectively) ( p < 0.001). Conclusions: Our study suggests that Hispanic callers under-utilize the 911 system, and when they do call 911, there are significant delays in initiating CPR.